African urbanization: an analytic policy guide - Collier, P (Oxford University Press, 2017)
Africa is rapidly urbanizing: it is the most important structural transformation under way in the region. By 2050, almost regardless of government policies, its urban population will have tripled. But the consequences are critically dependent upon policy choices: successful urbanization requires active and far-sighted government. At its best, urbanization can be the essential motor of economic development, rapidly lifting societies out of mass poverty. At its worst, it results in concentrations of squalor and disaffection which ferment political fragility. To date, African urbanization has been dysfunctional, the key indication being that cities have not generated enough productive jobs. If urban policies remain unchanged, future urbanization is likely to result in similar outcomes. This paper sets out how changed policies can unlock the potential of urbanization for prosperity. Primarily, it sets out the economic forces underlying this potential, and the specific policy actions they require. But policy actions do not just happen: they are generated by political processes that confer authority and capacity on public institutions. The paper concludes with a discussion of how politically urban policy-making might be improved.